Heavy metal and trace element contents in edible muscle of three commercial fish species, and assessment of possible risks associated with their human consumption in Saudi Arabia - El-Bahr, Sabry Mohamed; Abdelghany, Ahmed (Journal of Advanced Veterinary and Animal Research, 2015)
Three different highly consumed fish species from Al-Ahsa market, Saudi Arabia namely Spangled emporer (Lethriuns nebulosus), Red striped seabream (Pagrus major) and Black seabream (Spondyliosoma cantharus) were evaluated for their muscle contents of heavy metals (e.g., Cd and Pb) and trace elements (e.g., Cu, Zn, Fe and Mn). The possible risks associated with their human consumption were also studied. A total of 60 fresh fish samples comprising of 20 samples from each above mentioned fish were collected, and were subjected for determination of heavy metal and trace element contents by Atomic Absorption Spectrophotometry after Microwave Wet Digestion. The results showed that, accumulation patterns of the heavy metals and trace elements followed the order: Fe > Zn > Cu > Mn > Pb > Cd. There were variations among metal contents in the muscles of the three fish species; S. cantharus accumulated the highest levels of Cu, Zn and Mn, while the highest level of Fe could be detected in the muscles of P. major. The concentration of Cd and Pb remained comparable in the muscles of all three fish species. The calculated maximum daily intake (MDI) values were found as 0.0003, 0.0009, 0.0035, 0.0001, 0.0000, 0.0000 mg/day/person for Cu, Zn, Fe, Mn, Cd and Pb, respectively. Conclusively, the present study indicated that, fish muscles contain relatively less burden of heavy metals and trace elements, and no health problem can be raised from human consumption of the examined commercial fishes at Al-Ahsa market, Saudi Arabia. DOI: http://dx.doi.org/10.5455/javar.2015.b85